Increased efficacy of biologics following inhibition of autophagy in A549 lung cancer cells in bimodal treatment of doxorubicin and SAR405-loaded chitosan nanoparticles - Alamassi, Mohammed Numan; Chia, Suet Lin; Che Abdullah, Che Azurahanim; Masarudin, Mas Jaffri (Elsevier, 2023)
Conventional anti-cancer drugs, including doxorubicin, are associated with high toxicity and non-specific distribution in the body which results in a cascade of side effects. Cancer cells can utilize autophagy to promote tolerance to the stress induced by anti-cancer agents; this may be the major cause of drug resistance in advanced tumors. Owing to the molecular dynamism of cancer cells, targeting the pro-apoptotic survival pathways such as autophagy may increase the effectiveness of existing therapeutic agents at lower concentrations, thereby reducing the side effects of such agents. SAR405 is an inhibitor of autophagy activity due to its molecular interactions within the ATP binding site; however, it suffers from extracellular premature degradation and poor cellular uptake. Conversely, chitosan nanoparticles are considered biologically degradable, non-toxic, and biocompatible drug delivery agents that can be used to minimize the side effects of conventional therapeutic agents whilst increasing their intracellular uptake. In this study, a binary therapeutic strategy for the enhancement of the efficacy of doxorubicin while simultaneously inhibiting autophagy via a nano-mediated delivery system is reported. Autophagic inhibition was achieved via the improvement of SAR405 cellular uptake using SAR405-loaded chitosan nanoparticles. The synthesized nanoparticles were subsequently characterized for parameters of hydrodynamic diameter and polydispersity, while encapsulation and drug loading efficiencies were determined. Morphological characterization of the nanoparticles was elucidated using electron microscopy, and the cytotoxicity of the SAR405-loaded chitosan nanoparticles in combination treatments with doxorubicin was assessed through MTT and Annexin-v apoptosis assays. Autophagy progression through autophagosome formation was also evaluated using CYTO-ID staining. Following encapsulation, the size of the SAR405-loaded chitosan nanoparticles significantly increased from 54 nm to 161 nm at 10 µM SAR405 concentration, while the polydispersity index increased from 0.11 to 0.31 denoting presence of both encapsulated and unencapsulated moieties. When A549 lung cancer cells were treated with the IC50 values of doxorubicin in combination with SAR405-encapsulated CNP, an approximately 47% more reduction in cell viability was observed via the Annexin V-FITC/PI assay compared to using doxorubicin alone. Inhibition of autophagy was also detected in cells treated with SAR405 delivered using the nanoparticle system and was thought to be the primary reason towards a decrease in the resistance of the cancer cells to doxorubicin and thus increased its efficacy at lower concentrations. Therefore, this study has demonstrated a potential way of targeting cancer cell survival pathways that can be considered an effective way of increasing the efficacy of chemotherapeutic drugs.